2020
DOI: 10.3390/nu12051263
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Aqeel, M.; et al. “The Effect of Timing of Exercise and Eating on Postprandial Response in Adults: A Systematic Review”. Nutrients, 2020, 12, 221

Abstract: We would like to submit the following corrections to our recently published paper [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…One study found that young people who fasted for 16 h a day over a 2-month period with resistance training had a reduction in body fat percentage while maintaining muscle mass; 41 and a systematic review of 332 subjects showed that postprandial exercise was more effective in preventing hyperglycemia and enhancing insulin sensitivity than preprandial exercise. 42 Thus, IF combined with exercise can improve the aerobic capacity of skeletal muscle, resulting in greater weight loss and providing more health benefits than IF 24 or exercise alone. 38 …”
Section: If Combined With Other Interventionsmentioning
confidence: 99%
“…One study found that young people who fasted for 16 h a day over a 2-month period with resistance training had a reduction in body fat percentage while maintaining muscle mass; 41 and a systematic review of 332 subjects showed that postprandial exercise was more effective in preventing hyperglycemia and enhancing insulin sensitivity than preprandial exercise. 42 Thus, IF combined with exercise can improve the aerobic capacity of skeletal muscle, resulting in greater weight loss and providing more health benefits than IF 24 or exercise alone. 38 …”
Section: If Combined With Other Interventionsmentioning
confidence: 99%
“…Post-meal exercise is also beneficial in normoglycemic individuals and adults with overweight and obesity (Aqeel et al 2020). For example, 60 min of moderate-intensity continuous cycling at 65% VO 2peak performed after, but not before, a mixed-macronutrient meal reduced insulin AUC in males with obesity (Edinburgh et al 2020).…”
Section: Influence Of Acute Exercise-nutrient Timing On Postprandial Glycemic Excursionsmentioning
confidence: 99%